FAKTOR LINGKUNGAN BIOTIK DALAM KEJADIAN LUAR BIASA LEPTOSPIROSIS DI KABUPATEN TANGERANG, BANTEN, INDONESIA - Arief Nugroho; Wiwik Trapsilowati; Bernadus Yuliadi; Siska Indriyani (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Leptospirosis is a zoonotic disease caused by Leptospira . Leptospirosis is a public health problem throughout the world, including in Indonesia. The case of leptospirosis in Tangerang District in 2015 was increased the most cases located in the area of Puskesmas Kronjo . Environmental factors affect the spread of leptospirosis disease one of the biotic factors. The aim of the study to analyze the relationship of biotic environmental factors to the incidence of leptospirosis in Tangerang Regency. The research was conducted by cross sectional with location observation approach, and observation by questionnaire of biotic environment of resident's house. The number of house samples for biotic environmental inspection were 35 houses.The data collected includes the presence of pets at home, and plants around the house. Data on the success of rat catching was done by catching rat at the site. Data were analyzed descriptively and bivariate analysis. The results showed that vegetation (OR = 1,103, 95% CI = 0,987-1,234, p = 0,579) and pets (OR = 0,567; 95% CI = 0,47-6,895; p = 0,653) were statistically unrelated to the incidence of leptospirosis. The high trap success at the study site may be a potential risk for leptospirosis events.